A follow-up study of the teachers of BRAC schools who lost their job due to shifting of school - Khan, Md. Kaisar Ali (BRAC Research and Evaluation Division (RED), 2020)
This study aimed at examining the changes that occur in the lives of the former teachers of BRAC schools who lost their job due to the shifting of schools after completion of the cycles. A total of 386 ex-teachers was selected randomly from 32 team offices and' interviewed with a structured questionnaire. Findings show that about 72 % of the teachers could use their teaching skills although they did not have schools. Sixty-three percent of the teachers perceived that their social status remained static, 25% perceived an increase, and 13% perceived a decrease. Seventy six percent of them expressed that due to the shifting of school their mobility decreased, while 15% reported an increase. Forty-nine percent of the teachers were found to be employed and the rest were unemployed. Seventy five percent of the teachers became economically poorer due to the incident, but majority of them who were employed, had benefited economically. Amongst those employed, 71% were engaged in tuition and teaching and the rest were engaged in services for NGOs, handicrafts, poultry rearing, etc. The employment status of the teachers was found to be an influential factor for changing social, economic and mobility status. Since employment is closely related to their economic and social development, they should be given opportunity to be engaged in income-earning activities to better their livelihoods.